2010
DOI: 10.1177/0960327110363335
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical toxicology of salmeterol hydroxynaphthoate

Abstract: An extensive toxicology programme on salmeterol hydroxynaphthoate (SereventTM), a marketed long-acting β2-adrenoceptor agonist, has been carried out. The studies evaluated both the local (respiratory tract) and systemic tolerance to single and repeated dosing, effects on all stages of reproduction, as well as the genotoxic and oncogenic potential. High acute doses were well tolerated and caused no specific target organ toxicity. In repeat dose studies, animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…β 2 -Agonists. Foamy macrophage responses seen in rats exposed to β 2 -agonists (Owen et al, 2010) may be explained by the presence of β 2 -adrenergic receptors on ATII cells and consequent increased surfactant synthesis and its subsequent phagocytosis (Chander and Fisher, 1990;Mason and Voelker, 1998;Rooney, 2001). Corticosteroids have been shown to upregulate these receptors (Mason and Voelker, 1998;Salonen and Matilla, 1984).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…β 2 -Agonists. Foamy macrophage responses seen in rats exposed to β 2 -agonists (Owen et al, 2010) may be explained by the presence of β 2 -adrenergic receptors on ATII cells and consequent increased surfactant synthesis and its subsequent phagocytosis (Chander and Fisher, 1990;Mason and Voelker, 1998;Rooney, 2001). Corticosteroids have been shown to upregulate these receptors (Mason and Voelker, 1998;Salonen and Matilla, 1984).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…The extensive animal-based research makes it clear that the administration of ß-agonists (especially in high doses) can produce significant undesirable physiological adverse effects that are likely to deleteriously affect athletic performance in the long term. The most frequently adverse effects associated with the use of salmeterol include nausea, headaehes, muselé tremor, palpitation, muscle eramp, peripheral vasodilatation, tachycardia, and myocardial infarction (29). Moreover, it has been demonstrated that the ß2-AR agonist elenbuterol is capable of inducing myocyte apoptosis (3).…”
mentioning
confidence: 99%